RUANG PUBLIK DAN SENI PUBLIK - Jabaril, Rahmat (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Public Space and Public art, are two different senses. Public Space is a space that can be spread out because of the existence of a community that has the imagination that engages in it. Society is created and creates public space as a real democratic space. This is because, every actor in it interferes with imagination, and ideas that make that space continue to be spread out as public space. Public art is unconstitutional, so its beauty is a dynamic process. In that, then the public space and the art of public are compounds which have no meaning. Often it is not revealed that what we see on the streets, for example, provides reflective space and gives inspiration to the street performers. Public art, public space and public actors will make public dynamics an aesthetic form.